Pengembangan Modul Peradilan Hak Asasi Manusia Internasional Berbasis Learning Cycle 7e - Sari, Lavita Permata Arni; Sukowiyono, Sukowiyono; Awaliyah, Siti (Universitas Negeri Malang, 2023)
This study aimed to produce an appropriate, attractive, and effective learning cycle 7e-based international human rights justice module. The research and development model used in this study refers to the steps of Borg & Gall. The test subjects in this study were 47 class D students of the Pancasila and Civic Education Study Program, Universitas Negeri Malang. The module feasibility test was based on the validation results of material experts at 84.8 percent, media experts at 93.3 percent, and learning experts at 83.3 percent. The module's attractiveness level is based on the results of small-group trials of 98.5 percent and large group trials of 94.7 percent. The module effectiveness test was obtained from the results of the large group trials, namely the pre-test average value of 67.38 and 83.21 post-test. Based on the trial results, it showed that there was an increase in student learning outcomes of 15.83. It indicated that there had been a significant difference between student learning outcomes before and after using the developed module.